Clinical utility of fixed-combination telmisartan–amlodipine in the treatment of hypertension - Segura J; Ruilope LM (Dove Medical Press, 2011)
Julian Segura, Luis M RuilopeHypertension Unit, Hospital 12 de Octubre, Madrid, SpainAbstract: The majority of hypertensive patients, especially those with target organ damage, are likely to require multiple-drug therapy in order to reach blood pressure (BP) targets and reduce their risk of adverse vascular outcomes. The rationale for combination therapy with agents that block the renin–angiotensin system (RAS) and a calcium channel blocker (CCB) or diuretic is well founded in growing evidence. Recent published trials have shown that the combination of an RAS suppressor and a dihydropiridinic CCB would offer additional benefits independently of BP reduction. A telmisartan–amlodipine combination has demonstrated significantly greater BP reductions compared with each monotherapy component in the overall population, and in particular in patients with moderate to severe hypertension and high-risk patients. This combination is well tolerated with a safety profile similar to placebo and is consistent with the known safety profile of its monotherapy components.Keywords: hypertensive patients, monotherapy, stroke, antihypertensive